2019
DOI: 10.1109/jphot.2019.2946731
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Solar-Blind Ga2O3 Ultraviolet Photodetectors With High Responsivity and Photo-to-Dark Current Ratio

Abstract: In this work, flexible solar blind Ga 2 O 3 ultraviolet photodetectors with high responsivity and photo-to-dark current ratio are demonstrated. The Ga 2 O 3 films are obtained by the RF magnetron sputtering method on flexible polyimide (PI) substrates and the results demonstrate that all the films grown under various temperatures are amorphous. When the incident light wavelength is less than 254 nm, the incident light is effectively absorbed by the Ga 2 O 3 film. By controlling the growth temperature of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Solar-blind region refers to the ultraviolet (UV) radiation with wavelengths of 200-280 nm from the sun, which is strongly absorbed by ozone in the atmosphere and almost nonexistent at the Earth's surface. Photodetectors (PDs) operating in this region without interference from solar radiation have a significant application value in civil and military areas [1][2][3][4]. Recently, Ga 2 O 3 has gained added interest as a promising candidate for solar-blind photodetection because of its wide bandgap of 4.5-4.9 eV, good chemical and thermal stability [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Solar-blind region refers to the ultraviolet (UV) radiation with wavelengths of 200-280 nm from the sun, which is strongly absorbed by ozone in the atmosphere and almost nonexistent at the Earth's surface. Photodetectors (PDs) operating in this region without interference from solar radiation have a significant application value in civil and military areas [1][2][3][4]. Recently, Ga 2 O 3 has gained added interest as a promising candidate for solar-blind photodetection because of its wide bandgap of 4.5-4.9 eV, good chemical and thermal stability [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports also determine that an enhanced V oc of PSCs could be achieved with the introduction of ultrawide band gap ETLs. 22,23 Among these ultrawide band gap semiconductor materials, because of its unique advantages such as inexpensiveness, excellent thermal and chemical stability, ultrawide forbidden bandwidth between 4.6 and 5.3 eV, high transmittance, and high electron mobility, 24,25 Ga 2 O 3 has developed rapidly recently and is common in the fabrication of photodetectors and other optoelectronic devices. However, it is rarely seen that Ga 2 O 3 is applied during the exploration of PSCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These semiconductor materials generally have superior light transmission characteristics, excellent charge-transporting properties, and appropriate energy band levels which are expected to have the ability to improve the selectivity of the electrode and thus reduce the carrier recombination in PSCs. Previous reports also determine that an enhanced V oc of PSCs could be achieved with the introduction of ultrawide band gap ETLs. , Among these ultrawide band gap semiconductor materials, because of its unique advantages such as inexpensiveness, excellent thermal and chemical stability, ultrawide forbidden bandwidth between 4.6 and 5.3 eV, high transmittance, and high electron mobility, , Ga 2 O 3 has developed rapidly recently and is common in the fabrication of photodetectors and other optoelectronic devices. However, it is rarely seen that Ga 2 O 3 is applied during the exploration of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al demonstrated a process of tuning temperatures (50–200 °C) during the Ga 2 O 3 film fabrication by RF‐magnetron sputtering, where the Ga 2 O 3 film remained amorphous structure. [ 46 ] At the highest temperature of 200 °C, the devices exhibited the best performance with responsivity of 52.6 A/W under 254 nm UV light illumination and the photo‐to‐dark current ratio of more than 10 5 . Interestingly, Wang et al fabricated Ga 2 O 3 film by RF‐magnetron sputtering with one step at a specific temperature range, where the film maintained a transitional state composing of both amorphous and crystalline phases.…”
Section: Uv Pds Using A‐gaox Thin Filmsmentioning
confidence: 99%